Just how important is a good season start? Overall team performance and financial budget of elite soccer clubs - Lago-Peñas, C.; Sampaio, J. (Journal of Sports Sciences, 2015)
The aim of the current study was (i) to identify how important is a good season start on elite soccer teams` performance and (ii) to examine whether this impact is related to the clubs` financial budget. The match performances and annual budgets of all teams were collected from the English FA Premier League, French Ligue 1, Spanish La Liga, Italian Serie A and German Bundesliga for three consecutive seasons (2010-2011 to 2012-2013). A k-means cluster analysis classified the clubs according to their budget as High Range Budget Clubs, Upper-Mid Range Budget Clubs, Lower-Mid Range Budget Clubs and Low Range Budget Clubs. Data were examined through linear regression models. Overall, the results suggested that the better the team performance at the beginning of the season, the better the ranking at the end of the season. However, the impact of the effect depended on the clubs` annual budget, with lower budgets being associated with a greater importance of having a good season start (P < 0.01). Moreover, there were differences in trends across the different leagues. These variables can be used to develop accurate models to estimate final rankings. Conversely, Lower-Mid and Lower Range Budget Clubs can benefit from fine-tuning preseason planning in order to accelerate the acquisition of optimal performances.